COMMUNITY ATTITUDE TOWARD OVERCOMING RABIES DISEASE IN BANJAR BATULUMBANG AND BANJAR BRAHMANA, SANGEH VILLAGE, ABIANSEMAL DISTRICT, BADUNG REGENCY, BALI - Aldian Bhagaswara Aris Nurmansyah; I Wayan Masa Tenaya; Anak Agung Ayu Mirah Adi (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Rabies is a zoonotic disease transmitted from animals to humans caused by a virus of the genus Lysavirus of the family Rhabdoviridae. On November 14, 2008, rabies first appeared in Bali Province in Badung Regency and spread gradually to all districts in Bali Province. This study aimed to determine community attitudes towards rabies prevention in Banjar Batulumbang and Banjar Brahmana. This study used an observational design, with a sample size of 90 households with dogs, 47 households in Banjar Batulumbang and 43 households in Banjar Brahmana, in Sangeh Village, Abiansemal Subdistrict, Badung Regency, Bali. Data collection was conducted by census (door to door) by interviewing households with dogs using a questionnaire. Banjar Batulumbang community had a community attitude score of 97.2% while Banjar Brahmana community had a score of 98.3%. The conclusion is that community attitudes in both locations are quite good, which can influence rabies control in those locations, so these attitudes need to be maintained or improved for rabies control.